Bcl‐xL represents a therapeutic target in Philadelphia negative myeloproliferative neoplasms. Issue 18 (13th August 2020) - Petiti, Jessica; Lo Iacono, Marco; Rosso, Valentina; Andreani, Giacomo; Jovanovski, Aleksandar; Podestà, Marina; Lame, Dorela; Gobbi, Marco De; Fava, Carmen; Saglio, Giuseppe; Frassoni, Francesco; Cilloni, Daniela
Abstract: Myeloproliferative neoplasms are divided into essential thrombocythemia (ET), polycythemia vera (PV) and primary myelofibrosis (PMF). Although ruxolitinib was proven to be effective in reducing symptoms, patients rarely achieve complete molecular remission. Therefore, it is relevant to identify new therapeutic targets to improve the clinical outcome of patients. Bcl‐xL protein, the long isoform encoded by alternative splicing of the Bcl‐x gene, acts as an anti‐apoptotic regulator. Our study investigated the role of Bcl‐xL as a marker of severity of MPN and the possibility to target Bcl‐xL in patients. 129 MPN patients and 21 healthy patients were enrolled in the study. We analysed Bcl‐xL expression in leucocytes and in enriched CD34+ and CD235a+ cells. Furthermore, ABT‐737, a Bcl‐xL inhibitor, was tested in HEL cells and in leucocytes from MPN patients. Bcl‐xL was found progressively over‐expressed in cells from ET, PV and PMF patients, independently by JAK2 mutational status. Moreover, our data indicated that the combination of ABT‐737 and ruxolitinib resulted in a significantly higher apoptotic rate than the individual drug. Our study suggests that Bcl‐xL plays an important role in MPN independently from JAK2 V617F mutation. Furthermore, data demonstrate that targeting simultaneously JAK2 and Bcl‐xL might represent an interesting new approach.